2023
DOI: 10.3390/ijms24086990
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Monobenzone-Induced Vitiligo Mouse Model by the Addition of Chronic Stress

Abstract: Vitiligo is a common primary, limited or generalized skin depigmentation disorder. Its pathogenesis is complex, multifactorial and unclear. For this reason, few animal models can simulate the onset of vitiligo, and studies of drug interventions are limited. Studies have found that there may be a pathophysiological connection between mental factors and the development of vitiligo. At present, the construction methods of the vitiligo model mainly include chemical induction and autoimmune induction against melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…By affecting immune cell infiltration, taVNS may help to reduce the attack of the immune system on melanocytes, counteracting the development of vitiligo. In addition, previous studies also have reported the successful construction of a chronic stress-induced vitiligo mouse model based on the monobenzone-induced model, in which psychological induction further suppressed melanocyte generation and affected mouse behavior [ 49 , 50 ]. The comprehensive regulation of taVNS may better align with the complex pathophysiological mechanisms of vitiligo, encompassing immune system abnormalities, melanocyte apoptosis, and psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…By affecting immune cell infiltration, taVNS may help to reduce the attack of the immune system on melanocytes, counteracting the development of vitiligo. In addition, previous studies also have reported the successful construction of a chronic stress-induced vitiligo mouse model based on the monobenzone-induced model, in which psychological induction further suppressed melanocyte generation and affected mouse behavior [ 49 , 50 ]. The comprehensive regulation of taVNS may better align with the complex pathophysiological mechanisms of vitiligo, encompassing immune system abnormalities, melanocyte apoptosis, and psychological stress.…”
Section: Discussionmentioning
confidence: 99%